Medicinal plants of the National Nature Park “Tuzlovski limany”: species diversity, approximate estimation of the resources (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The medicinal plant species diversity of the National Nature Park “Tuzlovski lymany” consists of 403 species from 76 families. It's 70,5 % of the total flora of the park and almost twice the proportion of medicinal plants in the Ukrainian flora (37 %). Families Lamiaceae (94,7 %), Brassicaceae (93,3 %), Apiaceae (87,5 %) and Asteraceae (74,0 %) are especially rich in medicinal plants. The annuals and biennials are dominated among the life forms (184 species, 45,7 %), there are 155 herbaceous perennials (15,8 % less). The proportion of woody plants is 12,7 % (51 species). Anthropophyton is the richest florotsenotype (130 species), followed by Steppophyton (98 species, 23.8%), Drymophyton is the third (74 species, 18,4 %). Medicinal flora of the NNP “Tuzlovski lymany” includes 47 officinal, 269 non-officinal and 87 potential medicinal species. The underground plant organs are medicinal plant material of nearly a fifth of all the plants (17,6 %), 68,7 % medicinal plants gives “herb” as medicinal material. Species with non-commercial reserves are dominated (228 species, 56,6 %), 137 species (34,0 %) don't have reserves, reserves of 24 protected species aren't available (6,0 %). Researves of 13 species are described as commercial. Two officinal species (Matricaria recutita, Conium maculatum) have commercial researves, 31 – non-commercial, 5 species havn't researves, researves of two species aren't available. The limitations in medicine plant collection are detailed in the park.
Keywords: flora, medicinal plants, steppes.